RELIGIOUS COPING DENGAN SUBJEKTIVE WELL –BEING PADA ORANG YANG MENGALAMI PSIKOFISIOLOGIS - Witrin Gamayanti (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2013)
Psychosomatic is physical disorder which is triggered by psychological factors. Current developing theory stated that any physical disorder triggered by psychological problems are categorized as psychosomatic disorder. This research aims to study religious coping and subjetive well being of people having psychosomatic. Result found that people who do not involve Allah SWT in solving theor problems are hardly get out from problem pressure. Consequently, it cause subjective well being is getting lower and give impact to repeated physical disorder.